Peran Mediasi Kepuasan Kerja Terhadap Pengaruh Budaya Organisasi dengan Komitmen Organisasional pada Dinas Satuan Polisi Pamong Praja Kabupaten Takalar - Rahayu Musfirah; Kustini Kustini; Daisy Marthina Rosyanti (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The research findings show that honorary employees of the Takalar Regency Civil Service Police Unit have a low level of organizational commitment, which has a negative impact on organizational effectiveness. The main objective of this study is to investigate the mediating effect of job satisfaction on the relationship between organizational culture and employee organizational commitment at the Civil Service Police Unit Office in Takalar Regency. This study uses a quantitative research methodology and a case study approach, with a sample size of 96 respondents obtained through a saturated sampling technique. The research data were collected through an online survey questionnaire using a Likert scale, and then analyzed using Partial Least Squares. The results revealed that organizational culture does not have a statistically significant direct effect on employee organizational commitment. However, organizational culture is proven to have a positive and significant effect on employee job satisfaction. Furthermore, job satisfaction is proven to have a positive and significant effect on employee organizational commitment. In addition, the findings indicate that job satisfaction can function as an effective mediator, influencing the relationship between organizational culture and employee organizational commitment.